2002
DOI: 10.1002/jmv.10235
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of echovirus 30 during a meningitis outbreak, demonstrated by direct molecular typing from cerebrospinal fluid

Abstract: Echovirus 30 is one of the enterovirus serotypes isolated most frequently in meningitis cases. The genetic diversity of echovirus 30 was investigated in patients hospitalised during an outbreak in 2000 in Clermont-Ferrand, France. A nested reverse transcription-PCR (RT-PCR) assay was developed for qualitative analysis of the echovirus 30 VP1 encoding sequence directly from cerebrospinal fluid. The viral sequences obtained for 22 patients were compared with those of virus isolates obtained from nine patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 37 publications
5
42
0
2
Order By: Relevance
“…5) is consistent with previous VP1-based (3,4,8,27,37,49) and combined VP1/ RF-based (27,32,53) investigations of E30 population change within individual countries, such as Spain, France, the United Kingdom, and the United States. In one of the earliest studies (37), successive emergence and extinction of VP1 groups 1 to 4 was observed between 1956 and 1998 although in all likelihood (based on the diversity within each group and the time spans involved) they must each have contained a number of separate RFs.…”
Section: Vol 83 2009 Echovirus Population Dynamics 2115supporting
confidence: 89%
See 2 more Smart Citations
“…5) is consistent with previous VP1-based (3,4,8,27,37,49) and combined VP1/ RF-based (27,32,53) investigations of E30 population change within individual countries, such as Spain, France, the United Kingdom, and the United States. In one of the earliest studies (37), successive emergence and extinction of VP1 groups 1 to 4 was observed between 1956 and 1998 although in all likelihood (based on the diversity within each group and the time spans involved) they must each have contained a number of separate RFs.…”
Section: Vol 83 2009 Echovirus Population Dynamics 2115supporting
confidence: 89%
“…In the current study we have used the 3Dpol group as a marker to identify different circulating populations of E30 recombinant forms. The data we have obtained add to previous investigations of E30 population turnover and geographical distributions based on the identification of E30 subpopulations by phylogenetic groupings in VP1 (1,3,4,8,37,49,59). The use of RF-and VP1-based classifications of E30 for these epidemiological investigations has its own advantages and disadvantages.…”
Section: Vol 83 2009 Echovirus Population Dynamics 2115mentioning
confidence: 55%
See 1 more Smart Citation
“…Of note, the clinical virology laboratory of our main city hospital which monitors infections due to enteroviruses (Bailly et al 2002) reported that enterovirus isolations from clinical samples, especially Coxsackie virus, were remarkably rare during the study period. This suggests that enterovirus circulation was not active at the time.…”
Section: Resultsmentioning
confidence: 99%
“…Outbreaks of viral meningitis due to Echovirus 30 have been reported in several countries, including Brazil [Joeia et al, 1999;Trallero et al, 2000;Baily et al, 2002;Thoelen et al, 2003;Bernit et al, 2004]. The identification of this enterovirus as etiological agent responsible for these outbreaks indicates an active worldwide circulation of this serotype in recent years [Diedrich and Schreier, 2001], Israel [Somekh et al, 2003] and Spain .…”
Section: Discussionmentioning
confidence: 99%